Nesting Biology of Odynerus albopictus calcaratus (Morawitz, 1885) and Odynerus femoratus de Saussure, 1856 (Hymenoptera: Vespidae: Eumeninae). (17th July 2013) - Fateryga, Alexander V.
Abstract : The nesting biology of Odynerus albopictus calcaratus and Odynerus femoratus was studied in the Crimea (south of Ukraine); 46 nests of O. a. calcaratus and 18 nests of O. femoratus were examined. Both species nest on horizontal ground surfaces. The nests are vertical burrows surmounted by turrets. Females use water during nest construction and retrieve mud pellets from the nest burrow; these pellets are of two distinct sizes: small ones are used for the turret construction and big ones are dropped away. Females hunt for larvae of curculionid beetles of the genus Hypera . Completed nests are sealed with demolished turrets and nest burrows are usually entirely filled with mud. The nests of O. a. calcaratus contain 1-2 cells; the nests of O. femoratus contain 1–10 cells. The turrets of O. a. calcaratus are curved, and opened sideward; the turrets of O. femoratus are straight, and opened upward. The nesting success is 83% in O. a. calcaratus and 55% in O. femoratus . Most of the wasps died due to abiotic factors (e.g., rain). The nest structures of the species in the genus Odynerus studied so far are compared, and the function of the nest turret is discussed.